Farmer Producer Organization: A Potent Tool for Paradigm Shift in the Farm Sector - Bhadwal, Shiwani; Thakur, Rajesh Kumar; Kumar, Virender (Journal of Agricultural Extension Management, 2022)
Since independence, Indian agriculture has progressed from chronic food scarcity to self-sufficiency. With an average holding size of 1.08 ha, approximately 86 per cent of farmers fall into small and marginal categories. Small and marginal farmers are uncompetitive in terms of getting the best value for their produce due to their fragmented holdings and disorganization. To overcome these constraints and make small holding farming a viable option, farmers need to integrate as farmer collectives. Farmer Producer Organizations (FPOs) are one of the most important institutional innovations for empowering alleviating poverty, and advancing farmers. The primary goal of FPOs is to provide farmers with a sustainable business sense and better market access. However, in order to realize their full potential, FPOs must be encouraged by policymakers and other stakeholders, as well as scaled up across the country to benefit smallholders. In addition, government and extension organizations can focus their efforts on capacity building to ensure proper operation and success of FPOs. To make available market and price data to FPOs, they must be linked with input companies, technical service providers, marketing/processing companies, etc. Besides, India’s emerging market and policy concerns offer potential aggregation benefits that accrue from production to any other activity feeding into the value chain. As a result, FPO is unquestionably a powerful institutional tool for a paradigm shift in the farm sector